A large dumbbell glossopharyngeal schwannoma involving the vagus nerve: a case report and review of the literature - Zhao, Hongyu (BioMed Central, 2008)
INTRODUCTION: Schwannoma arising from the glossopharyngeal nerve is a rare intracranial tumor. Fewer than 40 cases have been reported. Accurate pre-operative diagnosis and optimal treatment are still difficult. CASE PRESENTATION: We present one case of schwannoma originating from the ninth cranial nerve with palsies of the trigeminal nerve, facial-acoustic nerve complex, and vagus nerve in addition to ninth nerve dysfunction. Magnetic resonance imaging showed tumors located in the cerebellopontine angle with extracranial extension via the jugular foramen, with evident enhancement on post-contrast scan. Surgical management single-staged with the help of gamma knife radiosurgery achieved total removal. CONCLUSION: Glossopharyngeal schwannoma is devoid of clinical symptoms and neurological signs. High resolution magnetic resonance imaging may play a key role as an accurate diagnostic tool. A favorable option of approach and appropriate planning of surgical strategy should be the goal of operation for this benign tumor.